Government Regulations and Ansoff’s Growth Strategies: Financial Performance of Kenya’s Leather Industry - Waititu, Jecinta; Wambui, Maria; Kamande, Merclyline (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This study examines the moderating role of government regulations in the relationship between Ansoff’s generic strategies and financial performance in Kenya’s leather industry. The leather industry plays a vital economic role in Kenya, yet firms struggle with structural inefficiencies, import competition, and regulatory challenges. Prior work: The role of government regulations such as; tax incentives, trade policies, and export controls in shaping the effectiveness of these strategies has not been empirically evaluated, raising concerns about strategic management and policy effectiveness. Approach: Using a quantitative, descriptive-correlational design, primary data was collected via structured questionnaires from 71 senior managers across 15 tanneries, supplemented by secondary financial data (2019–2023). Results: Ansoff’s Generic Strategies (Coeff = 1.202, p = 0.05) independently enhanced financial performance, supporting their foundational role in strategic management. Government Regulations (Coeff = 1.493, p = 0.04) had a direct positive effect, suggesting that regulatory frameworks create a stable business environment conducive to growth. Implications: The findings highlight the need for strategic-regulatory alignment, suggesting that policymakers should enhance export incentives and quality standards to bolster industry competitiveness. Value: This study contributes to strategic management literature by empirically validating the institution-based view of strategy in an emerging market context.